ОСОБЕННОСТИ ДИЗАЙН – ПРОЕКТИРОВАНИЯ УНИВЕРСАЛЬНОГО КРЕСЛА ПОВЫШЕННОЙ КОМФОРТНОСТИ ДЛЯ ТРАНСПОРТИРОВКИ ПАССАЖИРОВ В УСЛОВИЯХ АРКТИКИ (World Science, 2016)
The article considers design features of a passenger chair of the increased comfort. It describes the main advantages of this model, such as ergonomic, functional, esthetic and technical characteristics.